SARS-CoV-2 and extracellular vesicles: An intricate interplay in pathogenesis, diagnosis and treatment - Sbarigia, C.; Vardanyan, D.; Buccini, L.; Tacconi, S.; Dini, L. (Frontiers in Nanotechnology, 2022)
Extracellular vesicles (EVs) are widely recognized as intercellular communication mediators. Among the different biological processes, EVs play a role in viral infections, supporting virus entrance and spread into host cells and immune response evasion. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection became an urgent public health issue with significant morbidity and mortality worldwide, being responsible for the current COVID-19 pandemic. Since EVs are implicated in SARS-CoV-2 infection in a morphological and functional level, they have gained growing interest for a better understanding of SARS-CoV-2 pathogenesis and represent possible diagnostic tools to track the disease progression. Furthermore, thanks to their biocompatibility and efficient immune activation, the use of EVs may also represent a promising strategy for the development of new therapeutic strategies against COVID-19. In this review, we explore the role of EVs in viral infections with a focus on SARS-CoV-2 biology and pathogenesis, considering recent morphometric studies. The common biogenesis aspects and structural similarities between EVs and SARS-CoV-2 will be examined, offering a panoramic of their multifaceted interplay and presenting EVs as a machinery supporting the viral cycle. On the other hand, EVs may be exploited as early diagnostic biomarkers and efficient carriers for drug delivery and vaccination, and ongoing studies will be reviewed to highlight EVs as potential alternative therapeutic strategies against SARS-CoV-2 infection.